Increased interface effects of PtFe alloy/CeO2/C with PtFe selective loading on CeO2 for superior performance in direct methanol fuel cell. (22nd February 2019) - Chai, Zhanli; Zhang, Caixia; Wang, Hui; Bi, Xi; Bai, Ping; Wang, Xiaojing
Abstract: Here, a simple two-step solvothermal approach has been employed to synthesize PtFe alloy (or Pt)/CeO2 /C with PtFe (or Pt) selective loading on CeO2 nanoparticles. In addition, the selective loading of PtFe alloy or Pt nanoparticles on the surface of CeO2 is achieved under weak alkaline environment, which is mainly attributed to the opposite electrostatic force between H + enriched on the surface of CeO2 particles and OH − covered with carbon supporters. As-prepared PtFe alloy (or Pt)/CeO2 /C catalysts with two-stage loading structures show more excellent electro-catalytic efficiency for methanol oxidation as well as duration compared with commercial Pt/C and PtCeO2 /C with random loading structure. Further, single-cell assembly based on Pt3 Fe/CeO2 /C as the anode catalyst exhibits a maximum power density of 31.1 mW cm −2, which is 1.95 times that of an analogous cell based on the commercial Pt/C. These improved performances with considerable low Pt content (<0.3 mg cm −2 ) are mainly ascribed to the abundant three phase interfaces (PtCeO2 carbon) induced by the selective and efficient dispersion of Pt nanoparticles on ceria. Graphical abstract: PtFe alloy/CeO2 /C with PtFe selective loading on CeO2 could be obtained in alkalescent environment and exhibit superior performance in direct methanol fuel cell.Image 1 Highlights: PtFe alloy (or Pt)/CeO2 /C catalysts are provided with selective loading structures. A simple two-step solvothermal approach has been employed. The selective loading behavior shows susceptibility to the pH value. Pt3 Fe/CeO2 /C catalyst exhibits optimal performances in MOR and DMFC.